PELATIHAN INOVASI PENGOLAHAN PRODUK TEH & KOPI DI DESA MARGAMULYA KECAMATAN PASIR JAMBU - Dendi Gusnadi; Eva Mardiyana; Ratna Gema Maulida (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service activity aims to provide training and knowledge about innovations in processing tea and coffee products to the people of Margamulya Village, Pasir Jambu District. This counseling is carried out with the main objective of improving the skills and knowledge of the community in producing high-quality tea and coffee products that can compete in local and national markets. This activity included a series of workshops, practical training, and interactive discussion sessions involving participants from various backgrounds, ranging from farmers to small entrepreneurs in the field of tea and coffee product processing. The materials presented included processing techniques, selection of quality raw materials, marketing strategies, and other aspects related to improving product quality. The results of this activity include increased knowledge and skills of participants in processing tea and coffee products, increased production and product diversification at the local level, and the creation of a network of cooperation between business actors in Margamulya Village. It is expected that this activity will have a significant positive impact on the development of local economic potential and the improvement of community welfare in the region